2005
DOI: 10.1111/j.1399-3062.2005.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B in renal transplant patients

Abstract: We found that occult HB is a condition present in our population of renal transplant patients and that HCV infection does not seem to be associated with occult HB infection in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
8
1
1
Order By: Relevance
“…Serological markers of HBV infection were not detected in either of these patients. The primary finding of the present study was a very low prevalence of OHB among kidney transplant recipients (1%), as previously observed in two similar studies, one by Peres et al (2005) and the other by Bae et al (2012); these studies found prevalence of 2% and 2.7%, respectively. The demographic and laboratory data for the OHB infection patients are shown in Table II .…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Serological markers of HBV infection were not detected in either of these patients. The primary finding of the present study was a very low prevalence of OHB among kidney transplant recipients (1%), as previously observed in two similar studies, one by Peres et al (2005) and the other by Bae et al (2012); these studies found prevalence of 2% and 2.7%, respectively. The demographic and laboratory data for the OHB infection patients are shown in Table II .…”
supporting
confidence: 89%
“…Peres et al (2005) used a nested PCR with a limit of detection of 104 copies/mL, whereas in the present study and the study by Bae et al (2012), the RT-PCR assays had lower limits of detection of 3 IU/mL (16 copies/mL) and 2 IU/mL (11 copies/mL), respectively. It is important to use a PCR assay with a low limit of detection because the VL is usually lower than 200 IU/mL (1000 copies/ml) in OHB patients according to Raimondo et al (2008) .…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Estudos comprovaram a existência de alta prevalência da IOB entre dialisados, entretanto a prevalência de IOB entre receptores de transplante renal é controversa 27,28,29,30,31,32 28,29 .…”
Section: Introductionunclassified